TRACER STUDY LULUSAN 2022 ILMU KOMUNIKASI UNIVERSITAS MUHAMMADIYAH PROF. DR. HAMKA - Khohar, Abdul; Prakoso, Bayujati; Hariyati, Farida; Tiara, Andys (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2024)
This research is the result of a tracer study survey of 2022 graduates of the Communication Science Study Program, Faculty of Social and Political Sciences, University of Muhammadiyah Prof. DR. HAMKA. The results showed that 39% participated in filling out the tracer study, meaning that it did not reach the target set by 50%. Then, on the side where large graduates are large, there are 64% working in private companies, and the suitability of the field of science with work shows 58% (medium), 38% (high), and 4% (low). This marks most of the relevance between the field of science and the world of work. However, in terms of other aspects, 70% of practicums during college support jobs for 2022 graduates, and 21% (low)/does not support graduate employment. These tracer study output aspects can be a comprehensive evaluation; maximizing practicum, curriculum, and lecture aspects. Keywords: Alumni, Tracer Study, Communication Science, Working World